2020
DOI: 10.5114/wiitm.2020.93210
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic negative pressure therapy and/or endobronchial valve for pleural empyema minimal invasive management: case series of thirteen patients and review of the literature.

Abstract: Introduction: Intrathoracic negative pressure therapy is an adjunct to standard methods of complex empyema management in debilitated patients. Nevertheless, the use of endoscopic one-way endobronchial valves to successfully close large bronchopleural fistulas in patients with advanced pleural empyema has been described in only a few case reports. Aim: To present our experience in managing complex pleural empyema using thoracostomy with intrathoracic negative pressure therapy and/or endobronchial valve implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A few case reports showed that thoracostomy with intrathoracic negative pressure therapy combined with endobronchial valve implantation could manage pleural empyema with broncho-pleural fistula [ 27 ], but in children this kind of treatment is technically complicated due to anatomical conditions (such as a narrow bronchial lumen).…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports showed that thoracostomy with intrathoracic negative pressure therapy combined with endobronchial valve implantation could manage pleural empyema with broncho-pleural fistula [ 27 ], but in children this kind of treatment is technically complicated due to anatomical conditions (such as a narrow bronchial lumen).…”
Section: Discussionmentioning
confidence: 99%
“…Empyema is of great importance to clinicians due to morbidity, mortality and hospital costs. Treatment options range from antibiotic therapy, thoracentesis, chest tube insertion, fibrinolytic therapy, intrathoracic negative pressure therapy and/or endobronchial valve implantation, to decortication with video-assisted thoracoscopic surgery (VATS) or thoracotomy [ 5 7 ]. The main goal in treatment is to increase lung expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal in treatment is to increase lung expansion. For this, it is aimed to drain the fibrin deposits by reducing the viscosity of the fluid in the thoracic cavity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%